2015
DOI: 10.1159/000381329
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Routing of Signal Hearing Aid versus Transcutaneous Bone Conduction in Single-Sided Deafness

Abstract: The aim of this study was to compare a contralateral routing of signal (CROS) hearing aid to a transcutaneous bone-anchored device in the same conditions. This prospective crossover study included 18 adult patients with a single-sided deafness (SSD). After a trial period of 60 days with CROS and 7 days with a transcutaneous bone-anchored device (Alpha 1®, Sophono, Boulder, Colo., USA) on a headband, 13 (72%) patients opted for Alpha 1, 2 patients for CROS, and 3 rejected both rehabilitation methods. Clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
1
17
1
7
Order By: Relevance
“…The CM may be a good alternative for patients with SSD, resulting in significantly better speech recognition in the most difficult listening situations, i.e., when noise is presented to the NH ear and speech to the SSD ear (S SSD N NH ) compared to the unaided condition. These results are comparable to those of the study of Leterme et al [2015], who investigated speech perception in noise in SSD listeners with another BCD on a headband (Alpha 1 ® ; Sophono, Boulder, CO, USA]. Their investigation in 18 adult SSD patients revealed a significant improvement in speech perception in noise with a BCD on a headband when the speech material was presented to the SSD ear and the noise from the front (S SSD N 0 ).…”
Section: Significantly Better Speech Perception In Noise In the CM Aisupporting
confidence: 80%
“…The CM may be a good alternative for patients with SSD, resulting in significantly better speech recognition in the most difficult listening situations, i.e., when noise is presented to the NH ear and speech to the SSD ear (S SSD N NH ) compared to the unaided condition. These results are comparable to those of the study of Leterme et al [2015], who investigated speech perception in noise in SSD listeners with another BCD on a headband (Alpha 1 ® ; Sophono, Boulder, CO, USA]. Their investigation in 18 adult SSD patients revealed a significant improvement in speech perception in noise with a BCD on a headband when the speech material was presented to the SSD ear and the noise from the front (S SSD N 0 ).…”
Section: Significantly Better Speech Perception In Noise In the CM Aisupporting
confidence: 80%
“…The study included only patients who were scheduled to be implanted with a hearing device regardless of inclusion into the study. Comparable protocols have been employed before to compare a transcutaneous bone conduction device ( Leterme et al., 2015 ) or an active middle-ear implant ( Boeheim, Pok, Schloegel, & Filzmoser, 2010 ; Sziklai & Szilvassy, 2011 ; Truy, Philibert, Vesson, Labassi, & Collet, 2008 ; Uziel, Mondain, Hagen, Dejean, & Doucet, 2003 ) to acoustic hearing aids. Also, passive ( Briggs et al., 2015 ) and active transcutaneous devices ( Reinfeldt, Hakansson, Taghavi, Fredén Jansson, et al., 2015 ) have been studied in comparison to external stimulation via headband.…”
Section: Discussionmentioning
confidence: 99%
“…The Sophono Alpha system is a bone-conductive transcutaneous implant that transmits the vibrations of the external processor thought an intact skin by means of a magnetic coupling. It was first described by Siegert [2011], and since then other papers have been published concerning the use of this device in different pathological conditions [Denoyelle et al, 2013;Escorihuela-García et al, 2014;Hol et al, 2013;Leterme et al, 2015;Magliulo et al, 2015;Siegert and Kanderske, 2013;Sylvester et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the Alpha 1 ® system has already been described for conductive or mixed hearing loss in adults and children [Escorihuela-García et al, 2014;Denoyelle et al, 2013;Hol et al, 2013;Magliulo et al, 2015;Siegert and Kanderske, 2013;Sylvester et al, 2013]. The first prospective clinical study comparing the Alpha 1 system to CROS hearing aids in SSD has recently been published [Leterme et al, 2015]. The authors showed that the Alpha 1 was preferred to the CROS in 72% of patients and that hearing performance was significantly improved when using the Alpha 1 system compared to the unaided condition, whereas there were no statistically significant differences when comparing the audiological outcomes of the 2 devices.…”
Section: Introductionmentioning
confidence: 99%